PEREMPUAN DALAM POLITIK (STUDI KASUS PARTISIPASI SELEBRITIS PEREMPUAN DALAM KOMUNIKASI POLITIK DI PARTAI-PARTAI ISLAM PADA PEMILU 2014 DI INDONESIA) - Mohammad Zamroni (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
This study was conducted to see the participation of celebrity women, especially OA board of Partai Persatuan Pembangun and the DR board of Partai Amanat Nasional in political communication in political parties and in the legislature that will be studied on the issue of celebrity women as a political communicator, a political message to be delivered, media political communication is used, political audiences it addresses, and analyzes the effects of political communication appears. The location of this research is done in the office of the DPP and the DPP PAN Jakarta and in the House of Representatives. This study was a single case study with a phenomenological approach and includes descriptive analytical research. Data collection techniques with in-depth interviews, direct observation, as well as reviewing documents and archives. Data analysis techniques performed by an interactive model.The results showed, First, the level of welfare of women, especially celebrities and DR OA actually nothing to worry about, even those above the average rate of other women's welfare. Second, not all access to economic resources, social and political for women available in both formal and informal institutions, including for OA and DR. Third, the current female celebrities including OA and DR more conscious and critical of the various forms of life, especially for urban communities with more advanced levels of education. Fourth, the role of women in the legislature and political parties has not been equivalent to the participation of men. Fifth, in particular female celebrities OA and DR does not have any equality in terms of control or the same power as with men, to change the conditions of the position, the future of themselves and the community. His relationship with political communication research findings indicate that some of their important roles performed include female celebrities; the role of women as a political communicator celebrities, political messages female celebrities, female celebrities media of political communication, political communication celebrities female audience, and the effects of political communication female celebrities including OA and DR.